Hemisection: A Window of Hope For Freezing Tooth - Usha Radke; Rajesh Kubde; Aditi Paldiwal (Case Reports in Dentistry)
Advances in dentistry, as well as the increased desire of patients to maintain their dentition, have led to treatment of teeth that once would have been removed. Mandibular first molars are the most commonly extracted teeth due to dental caries and periodontal disease. These teeth are the major standpoint for occlusion, and also have a wide pericemental area. Hence, any defect in the root either mesial or distal, extraction is the most common treatment planned. Under specific conditions, only the diseased part of the tooth can be extracted after an endodontic treatment. A modified fixed partial denture design is fabricated to splint the remaining portion of the tooth to adjacent teeth. This procedure though daunting can be easily achieved and maintained successfully.